Case report: Treatment-resistant depression, multiple trauma exposure and suicidality in an adolescent female with previously undiagnosed Autism Spectrum Disorder - Secci, Ilaria; Petigas, Lucie; Cuenod, Alexandra; Klauser, Paul; Kapp, Carole; Novatti, Audrey; Armando, Marco (Frontiers in Psychiatry, 2023)
High rates of co-occurring depression are commonly reported in youth with Autism Spectrum Disorder (ASD), especially in individuals without intellectual disability (ID). Depression in ASD undermines adaptive behavior and is associated with a higher risk of suicidality. Females with ASD may be particularly vulnerable due to their greater use of camouflaging strategies. Indeed, in comparison to males, ASD is underdiagnosed in females, despite higher rates of internalizing symptoms and suicidality. Trauma exposure may also play a role in the development of depressive symptoms in this population. Moreover, evidence for effective treatments of depression in autistic youth are lacking, with ASD individuals frequently experiencing low efficacy and side effects. We present the case of an adolescent female with previously undiagnosed ASD without ID, admitted for active suicidal plans and a treatment-resistant depression (TRD), occurred after a COVID-19 lockdown in the context of cumulative exposure to stressful life events. Comprehensive clinical assessments performed at intake confirmed severe depression with suicidality. Intensive psychotherapy and different changes in medications were carried out (SSRI, SNRI, SNRI + NaSSA, SNRI + aripiprazole), all of which were ineffective, with persistent suicidal thoughts, often requiring intensive individual monitoring. The patient was finally successfully treated with lithium augmentation of fluoxetine, with no side effects. During hospitalization she was also evaluated by an ASD specialized center, where a diagnosis of ASD was made according to the Autism Diagnostic Observation Schedule (ADOS) and the Autism Diagnostic Interview-Revised (ADI-R) scores, as well as to clinical judgment of a senior psychiatrist. The present case report shows that clinicians should not overlook undiagnosed autism as a possible cause of TRD, especially in females without ID, where higher rates of under diagnosis may be in part related to their greater use of camouflage. It also suggests that ASD underdiagnosis and resulting unmet needs may be involved in vulnerability to stressful experiences, depression, and suicidality. Furthermore, it shows the complexity of providing care to TRD in youth with autism, suggesting that an augmentation therapy with lithium, a commonly recommended therapeutic strategy for refractory depression in typically developing samples, may also be effective in this population.